Prevalence of Sexual Dysfunction in Women with Type 1, 2 Diabetes and Thyroid Disorder: A Cross-Sectional Study in Taif City, Saudi Arabia - Alshehri KM; Althobaiti RA; Alqurashi AI; Algethami NE; Alswat KA (Dove Medical Press, 2022)
Khalid M Alshehri,1 Raghad A Althobaiti,2 Athar I Alqurashi,3 Nada E Algethami,4 Khaled A Alswat5 1Medicine and Endocrinology, AlHada Armed Forced Hospital, Taif, Saudi Arabia; 2Obstetrics and Gynecology Department, Prince Sultan Military Medical City, Riyadh, Saudi Arabia; 3Internal Medicine Department, King Abdulaziz Specialist Hospital, Taif, Saudi Arabia; 4Medical College, Taif University, Taif, Saudi Arabia; 5Department of Medicine, School of Medicine, Taif University, Taif, 21944, Saudi ArabiaCorrespondence: Raghad A Althobaiti, Obstetrics and Gynecology Department, Prince Sultan Military Medical City, Al Sulaimaniah, Riyadh, Saudi Arabia, Tel +966 505388455, Email Ralthobaiti@hotmail.comBackground: Women with diabetes mellitus or thyroid disorders are at risk of sexual dysfunction. This study aimed to estimate the prevalence of female sexual dysfunction (FSD) in women with diabetes and/or thyroid disorders and the impact of disease control on the ASEX score.Methods: A cross-sectional study for female patients who had a routine clinic visits was included. The Arizona Sexual Experience Scale (ASEX) was used to evaluate for FSD. Those with a total score of ≥ 19 or scored ≥ 5 on any item or ≥ 4 on three items were considered to have FSD.Results: A total of 253 female patients with a mean age of 39.1 ± 7.3 years were included. Two-thirds of the participants have no FSD. More than half (57.7%) of the participants had a strong desire for sex, and about 20% of the participants were unsatisfied with their orgasm. Compared to those with no FSD, those with FSD had lower BMI (P = 0.375), more likely to have a master's degree or higher (P = 0.117), diabetes (P = 0.879), hypothyroidism (P = 0.625), diabetes-related microvascular and macrovascular complications (P = 0.049), higher HbA1c, fasting glucose, and TSH (P = 0.731, P = 0.161, and P = 0.561, respectively), lower total cholesterol and LDL (P = 0.368 and P = 0.339, respectively), and exercise more regularly (P = 0.929).Conclusion: FSD was highly prevalent in our study population. Those with type 1 diabetes had the highest ASEX scores. We showed non-significant negative correlations between total ASEX score and both BMI and TSH, as well as a non-significant positive correlation between total ASEX score and both HbA1c and fasting glucose value.Keywords: diabetes mellitus, thyroid disorders, female sexual dysfunction, prevalence